EP.TH.140Enhanced Recovery in Liver Surgery: Effect on Survival in Patients with Colorectal Liver Metastases. (28th October 2021) - Stefanova, Irena; Martinou, Eirini; Kumar, Rajesh; Riga, Angela; Worthington, Tim; Karanjia, Nariman
Abstract: Aims: Enhanced recovery after surgery (ERAS) has shown to reduce perioperative stress and improve short-term postoperative outcomes. However, little is known regarding the effect of ERAS on long-term oncological outcomes. This study aimed to investigate the impact of ERAS on overall survival in patients undergoing liver resection for colorectal liver metastases (CRLM). Methods: Between 2006 and 2014, 387 patients underwent liver resection for CRLM at Royal Surrey County Hospital. The ERAS protocol after liver surgery was implemented in 2011. Data regarding patients' demographics, oncological characteristics, long and short-term postoperative outcomes were obtained from a prospectively maintained institutional database. Comparative analysis was performed between the ERAS and non-ERAS patients. The primary objective was overall survival (OS) and secondary objective included identification of factors affecting OS. Results: The groups were similar in terms of demographics, primary and secondary disease oncological characteristics. Intrahepatic recurrence rates were comparable between ERAS and non-ERAS group (30.3% vs 27% p = 0.496). Patients in the ERAS group demonstrated better 3-year survival rates in comparison with the non-ERAS ones (78.2% vs 68%, p = 0.027). Although survival was better at 5-years as well, this did not reach statistical significance (54.2% vs 50%, p = 0.470). The Cox proportional hazards analysis showed that increased length of hospital stay (HR 1.338, 95% CI 1.039-1.723, p = 0.024) and operative time (HR 1.580, 95% CI 1.173-2.128, p = 0.003) were the only parameters associated with increased risk for worse OS. Conclusions: ERAS protocol may be associated with improved 3-year survival in patients undergoing liver surgery for CRLM.